PRINCIPLES OF WORKING WITH STUDENTS WHEN TEACHING PROBLEM SOLVING IN PRIMARY SCHOOL - Narimbetova Z. A.; Dairabay J. S. (Bright Mind Publishing, 2025)
This article analyzes the need to change the methodology of teaching simple tasks in elementary school, which should include a practice-oriented approach, interdisciplinary communication and deep integration into modern society.
Keywords: Method, problem, relevance, innovative, skills, didactic material, technology, arithmetic, task, comparison of numbers, expressions, sets, result.